Sympathetic innervation of inguinal white adipose tissue in the mouse - Huesing, Clara; Qualls-Creekmore, Emily; Lee, Nathan; François, Marie; Torres, Hayden; Zhang, Rui; Burk, David H.; Yu, Sangho; Morrison, Christopher D.; Berthoud, Hans Rudolf; Neuhuber, Winfried; Münzberg, Heike (Journal of Comparative Neurology, 2020)
Adipose tissue plays an important role in metabolic homeostasis and its prominent role as endocrine organ is now well recognized. Adipose tissue is controlled via the sympathetic nervous system (SNS). New viral, molecular-genetic tools will soon allow a more detailed study of adipose tissue innervation in metabolic function, yet, the precise anatomical extent of preganglionic and postganglionic inputs to the inguinal white adipose tissue (iWAT) is limited. Furthermore, several viral, molecular-genetic tools will require the use of cre/loxP mouse models, while the available studies on sympathetic iWAT innervation were established in larger species. In this study, we generated a detailed map for the sympathetic innervation of iWAT in male and female mice. We adapted iDISCO tissue clearing to process large, whole-body specimens for an unprecedented view of the natural abdominal SNS. Combined with pseudorabies virus retrograde tracing from the iWAT, we defined the preganglionic and postganglionic sympathetic input to iWAT. We used fluorescence-guided anatomical dissections of sympathetic nerves in reporter mice to further clarify that postganglionic axons connect to iWAT via lateral cutaneous rami (dorsolumbar iWAT portion) and the lumbar plexus (inguinal iWAT portion). Importantly, these rami carry axons that branch to iWAT, as well as axons that travel further to innervate the skin and vasculature, and their functional impact will require consideration in denervation studies. Our study may serve as a comprehensive map for future experiments that employ virally driven neuromodulation techniques to predict anatomy-based viral labeling.
CRIS-Team Scopus Importer:2020-10-09
Keywords: iDISCO; imaging; pseudorabies virus; sympathetic chain ganglia; tissue clearing; transsynaptic retrograde tracing